Assessing the Quality of Work Life of Garment Workers in Bangladesh: A Study on Garment Industries in Dhaka City. (Global Journal of Management and Business Research, 2015)
This paper caters to assess the satisfaction level of garment workers with their quality of work life highlighting the garments inside the Dhaka city in Bangladesh. The study includes20 garment industries in Dhaka city at random using lottery technique. Approximately 12 workers have been selected from each of the factories. Data have been collected using a structured questionnaire. The research factors include compensation, job security, and work load, career growth opportunity, working environment, job design, informal relationship and participation in decision making. The study analyzed the data obtained from the self-completion questionnaire. The analysis contains some statistical measurements as, mean, standard deviation, and variance along with a frequency distribution table for each data set. The findings indicates that the employees working in garments sector neither disagree nor agree with their quality of work life initiatives by authority of the garments and their quality of work life is tending toward the 'somewhat agree' stance. The ending up of the study highlights suggestions recommended by the respondents.
Keywords: demographic factors; quality of work life; the readymade garment workers; and Bangladesh